2019
DOI: 10.1161/strokeaha.119.025553
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 10-Year and Lifetime Stroke Risk in Chinese Population

Abstract: Background and Purpose— Risk assessment is essential for the primary prevention of stroke. However, the current available tools derived from Chinese populations are insufficient for individualized 10-year and lifetime stroke risk prediction. Our study aims to develop and validate personalized 10-year and lifetime stroke risk equations incorporating 4 large Chinese cohorts. Methods— We used 2 prospective cohorts of 21 320 participants with similar survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…With the acceleration of population aging, China has faced the biggest burden of stroke in recent years [4,5]. Stroke is the leading cause of death in China [6]. Predictive studies have found that the estimated lifetime stroke risk for individuals aged 25 years or more in China is expected to reach very high levels, and this will be a major concern for the prevention and management of stroke in the future [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the acceleration of population aging, China has faced the biggest burden of stroke in recent years [4,5]. Stroke is the leading cause of death in China [6]. Predictive studies have found that the estimated lifetime stroke risk for individuals aged 25 years or more in China is expected to reach very high levels, and this will be a major concern for the prevention and management of stroke in the future [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are several stroke prediction tools in China. However, traditional methods, such as the Cox proportional hazard model [6,8], are unable to effectively explore the complex non-linear relationships in data. Machine learning methods can learn complex structures by incorporating numerous variables with high dimensional data [9].…”
Section: Introductionmentioning
confidence: 99%
“…The China-PAR stroke risk prediction model is the most recent tool to identify high-risk stroke adults in China (9). The validity of this risk model among samples of different age ranges has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the stroke risk for each BLSA participant using the published models of the R-FSRS (15) and China-PAR 10year stroke risk models (9). Supplementary Table 1 presents the predictor variables used in the R-FSRS and China-PAR models.…”
Section: Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation